2020
DOI: 10.21203/rs.3.rs-61938/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Postpartum mood among universally screened high and low socioeconomic status patients during COVID-19 social restrictions in New York City.

Abstract: Introduction: The mental health effects of the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) and the Coronavirus disease 2019 (COVID-19) pandemic on postpartum women is of increasing concern among mental health practitioners. To date only a handful of studies have explored the impact of the pandemic during pregnancy and none have attempted explore the impact of pandemic related social restrictions on postpartum mood.Methods: Postpartum patients appearing to the Mount Sinai Health System for thei… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 40 publications
0
14
1
Order By: Relevance
“…Further, the median wage in London in 2019 was £38,272 (Office for National Statistics, 2019), putting a two-person household at approximately £76.5K; only 34% of our sample had a household income before tax of between £0-75K. Low SES is a known risk factor for PND, and lower SES has been found to increase the risk of depression among adults in the United States during the pandemic; thus it is possible the rate depressive symptoms based on our sample were an underestimate of the actual rates in London (although see Silverman, et al, 2020).…”
Section: Limitationsmentioning
confidence: 85%
See 2 more Smart Citations
“…Further, the median wage in London in 2019 was £38,272 (Office for National Statistics, 2019), putting a two-person household at approximately £76.5K; only 34% of our sample had a household income before tax of between £0-75K. Low SES is a known risk factor for PND, and lower SES has been found to increase the risk of depression among adults in the United States during the pandemic; thus it is possible the rate depressive symptoms based on our sample were an underestimate of the actual rates in London (although see Silverman, et al, 2020).…”
Section: Limitationsmentioning
confidence: 85%
“…Add to this parenting stresses which are arguably more common in the postnatal periodfor instance, sleep deprivation, postpartum pain, the need to learn/relearn skills such as breastfeeding -and it appears reasonable to suggest that postnatal mothers are at particularly high risk of depression during the ongoing pandemic. However, there are at least two studies reporting a decrease in postnatal depressive risk during the pandemic; southern Israeli women giving birth in quarantine showed lower PND prevalence (Pariente et al, 2020), as did mothers of lower socioeconomic status (SES) in New York (Silverman et al, 2020). Rather than casting doubt on our findings, these studies highlight the contextually specific impact of social distancing measures; the authors of the Israeli study speculate that the mothers in their sample benefited from greater family support in this context (Pariente et al, 2020), while lower SES mothers in New York appear to have benefited from both not having to work themselves and increased childcare support from partners forced to stay at home (Silverman et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 A history of mental illness was also strongly associated with developing postpartum depression, anxiety, or PTSD. 19,20 It was observed that mothers with lower social support from family or friends, single mothers, strained marital relationships, 17 higher number of children, 15,21 immigrants, lower-income families, 16,20,22 and working women, 23 victims of domestic abuse or who do not have access to protective services also had higher levels of PPD and anxiety. 6,24 Complications during delivery or admission of newborn to the neonatal intensive care unit, 6,20 lack of support in breastfeeding, 25 early use of formula, 12 were also associated with higher levels of PPD and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, social distancing and restrictive lockdowns enforced by governments, have limited maternal social support networks, as well as access to health care services; This in turn has increased maternal risk for the development of psychological disorders [10]. Nevertheless, with emerging data, it is important to note that unlike most studies, some suggest that the maternal change in mood symptomology during the pandemic is not universal and mainly related to maternal socioeconomic status and support [11]. The childbirth experience has also changed dramatically with the new regulations regarding COVID-19 screening, restricted number of partners and staff supporting the parturient, and the use of personal protective equipment (PPE).…”
Section: Introductionmentioning
confidence: 99%